This is a very basic question about equations but reading online courses about equations didn't clear up what I'm missing.

TLDR; How to get from $T = RC$ to $R = \frac{T}{C}$

Working on a Raspberry PI project where I need to determine the value of a resistor, I decided to use the the step response approach.

I found the the time T in seconds to charge a capacitor with a capacitance of C in Farads and a resistor with a resistance of R in Ohms could be determined using the following equation: $T = RC$

I need to able to calculate the resistance needed for a given T so I tried to swap the equation as follow

$T = RC$

$\frac{T}{R} = \frac{RC}{R}$

$\frac{T}{R} = C$

$\frac{T}{R} * T = CT$

$R = CT$

But considering the fact that I can't calculate R with this equation using the T given by $T = RC$ I obviously made a mistake somewhere.

After some messing around in excel I managed to get the correct equation by using $R = \frac{T}{C}$ but I can't understand how to mathematically swap between $T = RC$ and $R = \frac{T}{C}$

While I understand why dividing the time by the capacitance makes sense to find the resistance, I am very frustrated to not to be able to swap the equation correctly.

Question: Where am I going wrong in my reasoning ?

I haven't used proper calculus in years, so it's probably pretty obvious ... I feel like I should have a $\frac{1}{T}$ somewhere in there but I can't tell why not where ...

  • $\begingroup$ Welcome to Math SE. I'm not quite sure how you got from the line "$\frac{T}{R} * T = CT$" to "$R = CT$" since $\frac{T}{R} * T = \frac{T^2}{R}$, not $R$ as implied in the next line. $\endgroup$ – John Omielan Aug 18 at 0:51
  • $\begingroup$ Ah ! So that's where I'm going wrong. Can you give me a pointer on how to reduce $\frac{T}{R}$ to just R ? Now that you point it out it seems obvious that multiplying T by T would give T squared ... I believe dividing by T would give $R = \frac{C}{T}$ which still doesn't work... $\endgroup$ – Mathieu VIALES Aug 18 at 1:02
  • $\begingroup$ I'm not quite sure what you're asking & trying to do. What do you mean by "reduce"? Note that $\frac{T}{R}$ (which is $C$ based on your equation) and $R$ are quite different generally in terms of values, and even in terms of dimensions. $\endgroup$ – John Omielan Aug 18 at 1:07
  • $\begingroup$ I'll rephrase my question: How do I get an equation to calculate R using T and C from the equation $T = RC$ ? (Sorry for my improper use of "reduce", being french I'm not really used to the proper English terminology when it comes to calculus)(also, thanks for you time) $\endgroup$ – Mathieu VIALES Aug 18 at 1:10
  • $\begingroup$ From $T = RC$, or the same $RC = T$, dividing both sides by $C$, you have $R = \frac{T}{C}$. This is what you asked about originally. Next, just substitute the values of $T$ and $C$ in the right hand side, i.e., divide the value of $T$ by that of $C$, to get $R$. Does this make sense or am I misunderstanding something? $\endgroup$ – John Omielan Aug 18 at 1:13

You have the equation

$$T = RC \iff RC = T \tag{1}\label{eq1}$$

To get $R$ by itself, divide both sides by $C$. Since $\frac{C}{C} = 1$, it "disappears" from the left side. Thus, you get

$$\frac{RC}{C} = \frac{T}{C} \implies R\left(\frac{C}{C}\right) = \frac{T}{C} \implies R = \frac{T}{C} \tag{2}\label{eq2}$$

With $T$ and $C$, you can substitute them into the right hand side, i.e., divide $T$ by $C$, to get $R$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.